186k views
1 vote
Probably very easy but i do need some help asap

my calculations are not giving me the answer i'm supposed to receive which is
9y^3(3-y)

Probably very easy but i do need some help asap my calculations are not giving me-example-1
User Bsekula
by
5.1k points

1 Answer

2 votes

Answer:


\sf 9y^3(3-y)

Step by step explanation:


\sf 27y^3-9y^4

Factor out common term 9 :


\sf \implies 9(3y^3-y^4)

Apply exponent rule
\sf a^(bc)=a^(b+c)=a^ba^c :


\sf \implies 9(3y^3-y^(1+3))


\sf \implies 9(3y^3-y^1y^3)

Factor out common term
\sf y^3:


\sf \implies 9y^3(3-y^1)

Apply exponent rule
\sf a^1=a :


\sf \implies 9y^3(3-y)

User Feng Zhao
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.